SELEKSI KULTIVAR KEDELAI: PERSIAPAN PEMULIAAN TANAMAN DENGAN METODE KULTUR MIKROSPORA - Sumarmi Sumarmi (Agric, 2018)
Microspore culture method can be used as plant breeding program. The preparation of cultivars selection is an important step. The research starts with cultivated five cultivars of soybean i.e: Argomulyo, Grobogan, Wilis, Anjasmoro and Black Malika. The appearence of soybean plant was observed until flowering. Selection of plants based on: sum of flower bud every plant, anther midline, total and diameter of microspore every flower bud was measured by the ‘Optilab’ software. The development of microspore done with grouping of flower bud according long 2.02.5 mm, 2.6-3.0 mm, 3.1- 3.6 mm and 3.7-4.1 mm for chooses flower bud with the most late uninucleate microspore stadium. Result of the research shows that long of flower bud 2.6-3.6 mm contain 1847-2010 late uninucleate microspores, diameter 20 µm for 5 cultivars can be used for material of microspore culture. Anjasmoro cultivar, tall of plant gain 68 cm, sum of rame 7-9, anther midline 354.67±59.67 µm, number of microspores each flower bud 2003±216. Result of responsive qulity test with anther incubation on 340C temperature for 4 days represent the most of total viable microspore, 3.371±45 on Anjasmoro cultivar. Plant breeding by Anjasmoro cultivar is the most appropriate for microspore culture treatment.